2020
DOI: 10.1007/s10661-020-08252-y
|View full text |Cite
|
Sign up to set email alerts
|

Content of polycyclic aromatic hydrocarbons in soil in a multi-annual fertilisation regime

Abstract: The study assessed changes in the total 16 PAH (polycyclic aromatic hydrocarbon) content of soil which occurred in 1998–2009, during a multi-annual, manure-mineral and mineral fertilisation experiment, carried out in Bałcyny near Ostróda (Poland), according to a design unchanged since 1986 The study focused on the impact of multi-annual, diversified mineral fertilisation (N, P, K, Mg and Ca) compared to manure applied every two years at a dose of 40 t/ha. The four plants used in the crop rotation included suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
2
9
1
Order By: Relevance
“…It can be concluded that nitrogen deficiency in the soil increases the degradation of PAHs compared to the addition of Spill-Sorb alone. A similar observation was also found by MaCkiewicz-Walec [20] and Acuña et al [5]. The incorrect dosage of applied nitrogen may lead to an inappropriate effect of the degradation of organic pollutants.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It can be concluded that nitrogen deficiency in the soil increases the degradation of PAHs compared to the addition of Spill-Sorb alone. A similar observation was also found by MaCkiewicz-Walec [20] and Acuña et al [5]. The incorrect dosage of applied nitrogen may lead to an inappropriate effect of the degradation of organic pollutants.…”
Section: Discussionsupporting
confidence: 84%
“…Another very common method is the application of nitrogen fertilization to contaminated soils. Nitrogen improves the efficiency of organic pollutant degradation by serving as an initiator for oildestroying microorganisms [2,20]. Nitrogen as an essential nutrient maintains the microbial population in the soil and consequently increases the rate of hydrocarbon degradation [17].…”
Section: Introductionmentioning
confidence: 99%
“…Something similar occurred in our series with PAHs; although they were frequently detected, this was mainly due to the high sensitivity of the analytical method, because the concentrations detected were very low (mean ∑PAHs = 2.9 ± 7.2 ng g −1 , median = 0.0 ng g −1 ). These concentrations are considerably lower than those reported in highly industrialized countries or regions, in the order of 70 [63] to 50,000 times [64] lower. However, the levels of two contaminants (p,p'-DDE and p,p'-DDD) did attract our attention, not so much because of the frequency of detection, which was similar to that reported in other studies (>70% of the samples), but because of the high concentrations detected.…”
Section: Application To Agricultural Soil Samplescontrasting
confidence: 59%
“…Something similar occurred in our series with PAHs; although they were frequently detected, this was mainly due to the high sensitivity of the analytical method, because the concentrations detected were very low (mean ∑PAHs = 2.9 ± 7.2 ng g −1 , median = 0.0 ng g −1 ). These concentrations are considerably lower than those reported in highly industrialized countries or regions, in the order of 70 [ 63 ] to 50,000 times [ 64 ] lower.…”
Section: Resultsmentioning
confidence: 57%
“…Long-term studies on changes in the PAH content in agricultural soils as a function of long-term fertilization in an unchanged system, both with mineral fertilizers and in combination with manure, are very scarce in the literature. The previously published findings by Krzebietke et al [ 18 ] and Mackiewicz-Walec and Krzebietke [ 19 ] confirmed that manure was also a source of PAHs, especially in an area with a relatively low PAH contamination from air pollutants accumulating in the dust and eventually depositing on the soil surface [ 20 ]. Most studies, mainly of a monitoring nature, concern the impact of large urban agglomerations on the contamination of neighboring soils [ 21 , 22 , 23 ] or the management of waste containing PAHs.…”
Section: Introductionmentioning
confidence: 72%